ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN DAN PENGGUNAAN TEKNOLOGI PEMBAYARAN ELEKTRONIK BERGERAK DENGAN MENGGUNAKAN MODEL UTAUT. (STUDI KASUS PADA TEKNOLOGI M-DINAR PAYMENT SYSTEM) - Wahyu Meiranto (Jurnal Akuntansi Indonesia, 2012)
The purpose of this research is to analyze factors that influence behaviour intention to use technology information system and use behaviour technology information system using UTAUT (unified theory of acceptance and use of technology). That factors are performance expectancy,effort expectancy, perceived of credibility, social influence, and facilitating condition and moderated by age, gender and experience. Sample of this research is investment using services community (M-Dinar) through internet. One hundred and twenty four respondents using M-Dinar had participated in this research. The collecting data used a questionnaire survey that posted at facebook and sent it via electronic-mail. Data were analyzed using a Moderated Regression Analysis (MRA). The result showed only social influence that effecting behaviour intention to use M-Dinar technology significant. The other factors aren’t have significant influence to behavoiur intention to use M-Dinar technology.